2020
DOI: 10.1001/jamanetworkopen.2020.11760
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fine Particulate Matter and Risk of Stroke in Patients With Atrial Fibrillation

Abstract: Key Points Question What is the association between fine particulate matter measuring 2.5 μm or less (PM 2.5 ) air pollution and ischemic stroke in individuals with prevalent atrial fibrillation (AF)? Findings This cohort study including 31 414 individuals with AF found an association between PM 2.5 and prospective ischemic stroke risk in longitudinal, residential-level assessments in a large health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“… PM 2.5 Seoul, Korea 2007 364 patients Increased risk of rupture-prone coronary plaque Yang et al (2019) 7. PM 2.5 Allegheny County, Pennsylvania 2007 - 2015 31,414 individuals with atrial Fibrillation (AF) Associated with high risk of ischemic stroke Rhinehart et al (2020) 8. PM 2.5 Shanghai, China 2014 - 2016 1,016,579 participants outpatients Increased risk of cardiac arrhythmias Yang et al (2020) 9.…”
Section: Impact Of Pm On the Cardiovascular Systemmentioning
confidence: 99%
“… PM 2.5 Seoul, Korea 2007 364 patients Increased risk of rupture-prone coronary plaque Yang et al (2019) 7. PM 2.5 Allegheny County, Pennsylvania 2007 - 2015 31,414 individuals with atrial Fibrillation (AF) Associated with high risk of ischemic stroke Rhinehart et al (2020) 8. PM 2.5 Shanghai, China 2014 - 2016 1,016,579 participants outpatients Increased risk of cardiac arrhythmias Yang et al (2020) 9.…”
Section: Impact Of Pm On the Cardiovascular Systemmentioning
confidence: 99%
“…Some epidemiologic studies have demonstrated that both short‐term and long‐term PM2.5 exposures are associated with a higher risk of ischemic stroke, especially with stroke characterized by large artery atherosclerosis (LAA) and small vessel occlusion 5‐7 . A recent large cohort study provided further evidence that PM2.5 exposure may be associated with ischemic stroke in individuals with prevalent atrial fibrillation 8 . In addition, high exposure to particulate matter (PM) before stroke may be independently associated with 3‐month mortality and cerebral edema after intravenous thrombolysis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Bourdrel et al, a 10 µg/m 3 increment in the PM 2.5 concentration had an influence on admissions for stroke up to two days after the exposure [32]. Besides the direct influence on ruptures of plaques in arteries, cerebral infarction pathomechanisms may also include the induction of atrial fibrillation, the consequent formation of thrombi, and their release to the bloodstream reaching the brain vessels [33,34].…”
Section: Discussionmentioning
confidence: 99%